Guidelines for Caring for Incapacitated Teachers and Students at Former Jesuit Colleges in Europe - Kochanowicz, Jerzy (Journal of religion and health, 2025)
The aim of this article is to explore the regulations governing the treatment of incapacitated people in former Jesuit colleges in Europe, focusing on the academic staff and students residing in these institutions. This treatment was strongly influenced by the spirituality of Ignatius of Loyola, who perceived disease in dual terms: as an evil to be combated through all available means and as a test of faith from God. Ignatius instructed college superiors to prioritize the care of the sick and appointed specific officers within the community, such as prefects of health, nurses, and pharmacists, while also formulating detailed rules for the care and treatment of the sick. Understanding these principles, which served as a vademecum for nursing practices at the time, provides insights into the daily life of former Jesuit colleges and can serve as inspiration for modern approaches to patient care, particularly emphasizing the importance of attending to their mental well-being.